ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI EARNINGS RESPONSE COEFFICIENT (ERC) - Yunita Nursopiatin, Widyasari (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of research is to obtain empirical evidence about the impact of leverage, profitability, sales growth, and firm size to Earnings Response Coefficient (ERC) on manufacture companies listed on the Indonesia Stock Exchange (IDX) in 2016-2018. This study used 58 manufacture companies selected using purposive sampling method. The data used are secondary data in the form of financial statements. The statistical method used to test the research hyphotesys is the regretion panel data analysis model. The results of this research are leverage have negative and significant effect, sales growth have positive and significant effect, meanwhile profitability and firm size have insignificant effect to Earnings Response Coefficient (ERC).